Kinanthropometric and performance characteristics of elite and non-elite female softball players - Singh, S.; Singh, M.; Rathi, B. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The purpose of the present study was to compare the kinanthropometric and performance characteristics of elite and non-elite female softball players. Methods: A total forty elite and non-elite level female softball players were selected from the different colleges affiliated to the Guru Nanak Dev University, Amritsar, for the present study. The height of subjects was measured by using the standard anthropometric rod. Weight was measured with portable weighing machine. Widths and diameters of body parts were measured by using digital caliper. Girths and lengths were taken with steel tape. Skinfold thickness measurements were taken using the Slimguide skinfold caliper. All subjects were also assessed for performance tests i.e. vertical jump, 50m sprint, medicine ball throw, 10×4m shuttle run and reaction time. Results: Independent samples t-test reveals that elite female softball players were significantly taller. Conclusion: The elite female softball players had significantly greater kinanthropometric characteristics, body composition and performance characteristics than the non-elite female softball players.